Meningkatkan Kemampuan Coping Remaja melalui Penerapan Teori Sosial Kognitif dalam Praktik Bimbingan Konseling - Dedi Effendi; Neviyarni Neviyarni; Herman Nirwana (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Coping ability is the ability to cope with pressure and problems. there are several types of coping strategies, including passive and active coping. The purpose of this study is to see how social cognitive theory can be applied in guidance and counseling practice to improve adolescents' ability to handle stress. To find the application of the theory in guidance and counseling, relevant literature has been collected and analyzed using the literature review method. Results show that the principles of Cognitive Social Theory, which include strong social support, the use of active coping strategies, and parental involvement, contribute positively to the development of adolescents' coping skills. The results showed that adolescents who participated in a TSC-based guidance and counseling program showed better emotional resilience and self-efficacy. It was found that strengthening coping skills requires support from peers and family. To ensure that the intervention meets the needs of adolescents, ongoing evaluation is also needed. This study points out some issues when implementing a TSC-based guidance program, such as obtaining adequate training for counselors and ensuring that resources are available. It is expected that adolescents will be able to gain better skills to handle diverse situations and improve their emotional resilience by implementing an effective theory-based approach. Further research is needed, especially to improve adolescents' adaptability in today's increasingly complex environment.